Evolutionary concepts in end user productivity and performance applications for organizational progress - Clarke, Steve, 1950- (Advances in end user computing., 2009)
"This book aims to represent some of the most current investigations into a wide range of end-user computing issues, enhancing understanding of recent developments"--Provided by publisher.